Características mineraloquímicas e implicancias genéticas de la vesubianita del skarn Loma Marcelo, sierras australes de Buenos Aires - Ballivián Justiniano, Carlos A. (2013)
The vesuvianite from Loma Marcelo skarn, Sierras Australes of Buenos Aires province, was studied by petrography, X-ray diffractometry and energy-dispersive X-ray spectroscopy that allowed establishing P4/nnc crystal symmetry and the presence of fluorine. These findings point out a formation temperature around 500 °C and CO$latex ^{_{2}} $mole fractions higher than those for the stability field of the association vesuvianite + wollastonite.